Operation Orphan and Danbro: an SME–charity partnership. Issue 7 (3rd October 2021) - Russon, Jo-Anna; Moore, Brad; Broughton, Helen
ABSTRACT: This Practical Note reviews a long-term partnership between Operation Orphan–a small development charity–and Danbro–an accounting services firm. This partnership was formed in 2010 when Danbro committed to underwriting 100% of Operation Orphan's UK administrative costs, enabling other donations to directly support orphans and vulnerable children in Zimbabwe and beyond. We discuss the core elements underpinning the partnership: governance arrangements, trust, relationship and long-term financial commitment, and explore how issues of power and partnership sustainability are perceived and managed. The case concludes with a reflective note on the broader implications of this type of SME–charity partnership model.